2016
DOI: 10.1037/a0039687
|View full text |Cite
|
Sign up to set email alerts
|

Youth violence: What we know and what we need to know.

Abstract: School shootings tear the fabric of society. In the wake of a school shooting, parents, pediatricians, policymakers, politicians, and the public search for "the" cause of the shooting. But there is no single cause. The causes of school shootings are extremely complex. After the Sandy Hook Elementary School rampage shooting in Newtown, Connecticut, we wrote a report for the National Science Foundation on what is known and not known about youth violence. This article summarizes and updates that report. After dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
88
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 142 publications
(100 citation statements)
references
References 198 publications
(181 reference statements)
5
88
0
4
Order By: Relevance
“…The more time the children spent watching TV, playing video games or browsing the Internet the more they reported verbal, physical and electronic aggressive behaviors towards their peers. These results are in accor-dance with the previous research on peer violence (Bushman et al, 2016;Dittrick et al, 2013;Kuntsche, 2004;Zimmerman et al, 2005). Media violence effects were similar for both genders as well as for younger and older adolescents, which corresponds to some earlier studies (e.g., Huesmann et al, 2003;Valkenburg & Cantor, 2000).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The more time the children spent watching TV, playing video games or browsing the Internet the more they reported verbal, physical and electronic aggressive behaviors towards their peers. These results are in accor-dance with the previous research on peer violence (Bushman et al, 2016;Dittrick et al, 2013;Kuntsche, 2004;Zimmerman et al, 2005). Media violence effects were similar for both genders as well as for younger and older adolescents, which corresponds to some earlier studies (e.g., Huesmann et al, 2003;Valkenburg & Cantor, 2000).…”
Section: Discussionsupporting
confidence: 77%
“…Although experimental studies have found causal relationship between violence in media and aggressive behavior, the exposure to media is neither a necessary nor sufficient cause of youth's aggression (Bushman & Anderson, 2015). The media effects that have been found are larger for milder forms of aggression (d = 0.39) than for criminal behavior (d = 0.20) (Bushman et al, 2016). Concerning duration of effects, both immediate and long lasting effects of media violence have been found.…”
Section: Introductionmentioning
confidence: 93%
“…[1] comment that youths exposed to smoking or drinking media characters are more likely to start smoking or drinking themselves. They suggest that ‘research should test whether youth are more interested in acquiring and using guns after exposure to movie characters that use guns’ [1, p. 32]. In line with that suggestion, this study examined whether exposure to violent video games might foster interest in the acquisition of guns.…”
Section: Introductionmentioning
confidence: 99%
“…Such problems disproportionately affect males overall and African Americans males in particular, and are largely an urban phenomenon (3). Correlates of youth violence have been identified at the individual, family, peer/school, community and societal levels (47), including alcohol or drug use, neuropsychological deficits, chronic stress from exposure to violence, poor parent-child relationship, family conflict, and living in disadvantaged, disordered neighborhoods (8). Being relatively stable, these factors can help identify individuals predicted to face an elevated risk of being shot, and inform preventive interventions.…”
mentioning
confidence: 99%